-45=-3b

Simple and best practice solution for -45=-3b equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -45=-3b equation:


Simplifying
-45 = -3b

Solving
-45 = -3b

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '3b' to each side of the equation.
-45 + 3b = -3b + 3b

Combine like terms: -3b + 3b = 0
-45 + 3b = 0

Add '45' to each side of the equation.
-45 + 45 + 3b = 0 + 45

Combine like terms: -45 + 45 = 0
0 + 3b = 0 + 45
3b = 0 + 45

Combine like terms: 0 + 45 = 45
3b = 45

Divide each side by '3'.
b = 15

Simplifying
b = 15

See similar equations:

| h/10-40=-36 | | k-11=-2 | | 5x+-6=12+2x | | x(a-b)-4(a-b)=0 | | 46-(2x+8)=2(x+4)+x | | 20p^2-100pq+125q^2= | | 5x-6=1+2x | | q/2-2=8 | | 25z=5 | | g/2-1=1 | | 4(5v-4)=22+v | | 16p^2-40p+25= | | 2x^2=30x | | -3n+12-4n= | | 19=5t-16 | | 180+92x=250+78x | | 25c^2-9c=0 | | 8a+7=-65 | | 29=-59+4 | | 18x^5+15x^4z-75x^3z^2= | | 4n-14=62 | | (5a+2b)-(3a-2b)= | | 7a^2+22a+3=0 | | 30a^2+am-m^2= | | b+3.09=-5.91 | | 14.2+(-9.1)= | | 8y+6=-50 | | 9x-8+4x=7x+14 | | 12=6-2x | | 1-3x=-10 | | (-3)-2y=9 | | 9a^2+27a=0 |

Equations solver categories